2016
DOI: 10.21829/myb.2004.1031263
|View full text |Cite
|
Sign up to set email alerts
|

Plan de manejo para el manglar de Sontecomapan, Catemaco, Veracruz, México: una estrategia para la conservación de sus recursos naturales

Abstract: El manglar de Sontecomapan, ubicado en la Reserva de Biosfera Los Tuxtlas, al sur del estado Veracruz, forma parte del patrimonio natural de México y del mundo. Actualmente, se encuentra inscrito en la Lista Ramsar con el número 1342. Su importancia se reconoce en términos biológicos, culturales y económicos. Su valor biológico está fundamentado en el papel que este ecosistema representa para numerosas especies animales y vegetales, al funcionar como hábitat, refugio y zona de anidación y desove. Una caracterí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
2
1
0
1
Order By: Relevance
“…The higher density of L. racemosa coincides with that found in basin mangroves where, with greater distance inland, the tidal influence decreases, and the density of R. mangle diminishes, while that of L. racemosa and A. germinans increases [32]. The mangrove species were consistent with those recorded in Tabasco by Torres et al [52] and Torres et al [53] and in Veracruz by Carmona-Díaz et al [54] and Moreno-Casasola et al [55], comprising three of the six mangrove species recorded in Mexico. The density of mangroves is a function of growth and developmental stage due to competition for crown space [52].…”
Section: Tree Densitysupporting
confidence: 88%
See 2 more Smart Citations
“…The higher density of L. racemosa coincides with that found in basin mangroves where, with greater distance inland, the tidal influence decreases, and the density of R. mangle diminishes, while that of L. racemosa and A. germinans increases [32]. The mangrove species were consistent with those recorded in Tabasco by Torres et al [52] and Torres et al [53] and in Veracruz by Carmona-Díaz et al [54] and Moreno-Casasola et al [55], comprising three of the six mangrove species recorded in Mexico. The density of mangroves is a function of growth and developmental stage due to competition for crown space [52].…”
Section: Tree Densitysupporting
confidence: 88%
“…The density of mangroves is a function of growth and developmental stage due to competition for crown space [52]. The highest density associated with L. racemosa is consistent with that reported in Colima, Mexico, by Téllez-García et al [56] and by Torres-Fernández et al [54], who reported it as the species with the highest density. The low density of A. germinans coincides with that found by Torres et al [52], who reported that in Laguna Mecoacán, Tabasco, Mexico, A. germinans covers physiologically unfavorable areas (high salinity) and has a negative correlation with the densities of R. mangle and L. racemosa.…”
Section: Tree Densitysupporting
confidence: 81%
See 1 more Smart Citation
“…La presencia de este pez invasor en un ecosistema tan importante como lo es el manglar, que actúa como hogar, refugio e inclusive zona de desove y crianza de una gran variedad de organismos marinos (Carmona-Díaz et al, 2004), implica un riesgo debido a que la especie se caracteriza por ser un depredador activo que consume una gran cantidad de organismos de importancia comercial y/o ecológica, tales como especies de las familias Lutjanidae, Serranidae y Scaridae, entre otras Figura 2. Ubicación de la bahía de Chengue.…”
unclassified